The essential oils compositions of Iranian Oregano (Origanum vulgareL.) populations in field and provenance from Piranshahr district, West Azarbaijan province, Iran - Mohamad Pirigharnaei; Samad Zare; Reza Heidary; Jalil Khara; Reza EmamaliSabzi; Farshad Kheiry (Avicenna Journal of Phytomedicine, 2011)
Objective: Origanum vulgare L. is rarely cultivated in Iran but it is the only species of the Origanum genus growing wild in this country. O.vulgare L. is widely spread all over the country. In this study, parameters of content, composition and antioxidant activity of the essential oils of domestic and wild Iranian Oregano populations were compared  with one another. Materials and Methods: The extractions were performed using a clevenger-type apparatus and the essential oils in the Oregano plants were obtained by hydro-distillation and analyzed by GC/MS. Results: The essential oils were obtained in the Oregano field at yield of (0.80%) and the 4 provenance Oregano (ranging from 0.93% to 1.66% v/w). In cultivated plant 22 constituents, representing 94.02% and in 4 provenance plants (O.v-w1--- O.v-w4), 21, 25, 22, 20 constituents, representing 96.55%, 95.66%, 95.8%, 94.48% of the oils, respectively, were identified. The two major constituents of the essential oils, carvacrol ranging from 23.54 to 67.09% and, γ-terpinene ranging from 7.71 to 20.94% were present in relatively equal amounts in all five samples from different localities. Five chemotypes of essential oils were identified. The main chemotype was carvacrol-γ-terpinene. Furthermore, the antioxidant activity of essential oils of O.vulgare using DPPH radical scavenging was determined. All extracts exhibited almost the same pattern of antioxidant activity as ascorbic acid (vit C). Conclusion: Our findings demonstrated that the chemical composition of the essential oils of O. vulgare L. varies considering geographical location of collection site, climate and other ecological conditions which suggest both intrinsic/genetic and extrinsic/environmental factors such as: altitude, edaphic, temperature, humidity and climate, may play important roles in determining the oils composition.